RAPD Primers Selection for Genetic Variation Analysis of Banana Plant (Musa spp.) - Wiguna, I Ketut Catur; Pharmawati, Made (Universitas Andalas, 2021)
Identification of genetic diversity using molecular markers is important for basic information for plant conservation. Banana is a fruit bearing plants that important for food sources in human life. This study aimed to determine the optimum conditions of PCR-RAPD reaction and RAPD primers that suitable to amplify DNA fragmens. DNA isolation was done using modified of CTAB and chloroform isoamil alcohol. The samples used was young leaves of nine banana cultivar plants. Optimation was done using variety of DNA and MgCl2 concentration. Eight primers produced by Operon Primer Technology were tested. The DNA genomic concentration obtained was in the range of 23,3 ng/µl – 70 ng/µl. The optimum conditions of PCR-RAPD of banana plants that produce clear band were 50 ng/µl DNA template, 3 mM MgCl2 with the number of thermal cycles was 40 x. There were six RAPD primers that successfully amplified DNA : OPA 02, OPA 04, OPB 12, OPD 20, OPH 01, and OPH 03. The primer OPA-04 had the lowest resolving power value (4,4) , while OPH 01 had the highest (11,3) resolving power.